The relationship of gender and maternal socialization to delay of gratification among selected public school first graders - De Guzman-Capulong, Annalyn L. (2004)
The study investigated the relationship of gender and maternal socialization to delay of gratification among 7-8-year-old children as well as explored their self-generated strategies while waiting. A maternal survey questionnaire was developed to measure the mother's socialization of their children's delay behavior. Two measures of delay of gratification were used: delay to criterion (whether or not children were able to wait criterion time of 15 minutes) and delay time (actual time children were able to wait). Results showed that out of the 33 participants, 24 were able to wait (delayers) while 9 children were not able to do so (nondelayers). Delay time was significantly related to maternal socialization of delay behavior. It was also used significantly related to gender but among nondelayers only. Delayers successfully waited by attending to their hands, other body parts and objects inside the room while children with shorter delay time more frequently attended to the rewards and bell rather than elsewhere.
Includes bibliographical references (pages 43-44).